Consequences of the Economic and Monetary Union for the Coordination of Tax Systems in the European Union : Lessons from the U.S. Experience - Zee, Howell (IMF Working Papers; Working Paper ;, 1998)
With the advent of the economic and monetary union in the European Union (EU), the economic landscape of the EU will bear a striking resemblance to that of the United States in terms of fundamental attributes such as the freedom of internal movements of individuals, capital, and goods within the union, as well as the adoption of a common currency. This paper examines developments in the tax systems of the states in the United States and draws lessons for the need of coordination of EU tax systems.